Balanced scorecard aplicado aos projetos públicos de construção brasileiros: uma análise dos fatores críticos de sucesso - Cuzzuol, Fernando Leonel (2020)
It is well known that the Brazilian political and economic scenario has been going through difficult times since the last 5 years, many sectors have suffered the consequences of the crisis, and in the construction sector, as a thermometer of the economy, was no different. In this context, the present research work focused on the analysis of the main Critical Success Factors (CSF) associated with public construction projects, with subsequent application of the Balanced Scorecard (BSC) Performance Measurement System (PMS). For data collection, a survey was applied in September 2019. Data were measured with the 7-point Likert scale and evaluated with discriminant and exploratory analysis. As a result, it was identified the formation of two classes of relevance between the factors analyzed, with class “A” being the most important and class “B” the least. However, an isolated analysis of the class-split criteria was insufficient to describe the success of a public construction project. In this sense, a factorial analysis of the data was necessary, which resulted in the grouping of the studied factors into 13 components that considered the interdependence between the data and together more faithfully defined the success of a Brazilian construction public projects. The BSC translated the FCS into tactical and operational objectives with their respective indicators, targets and initiatives, in order to be consistent with the vision, mission and strategic objectives of the Ministry of Economy (ME), specifically those of the Secretariat for Infrastructure Development (SDI), responsible for the optimization and management of public projects.